EGGSHELL CALCIUM NANOPARTICLES: A SUSTAINABLE APPROACH TO BOOST BIOGAS PRODUCTION FROM TOFU LIQUID WASTE - Sari, Yessie Widya; Attar, Zia Rausyanfikr; Widyarani, Widyarani (Universitas Mataram, 2024)
This study explored enhancing biogas and methane production from tofu liquid wastewater (TLW) by adding calcium nanoparticles. Eggshell calcium nanoparticles (ECN) in the form of nano Ca (OH)2 were introduced to improve the degradation process. Chicken eggshells were calcined at 1000 °C to create Ca (OH)2 particles, followed by milling to yield ECN. Characterization using X-ray diffraction (XRD) confirmed the presence of Ca (OH)2 in the ECN while scanning electron microscopy (SEM) revealed the irregular morphology of the particles. Energy-dispersive X-ray spectroscopy (EDS) analysis showed calcium and oxygen as the primary elements. To investigate the effect of ECN in enhancing biogas and methane production, we evaluated 3 levels of ECN concentrations during anaerobic fermentation of TLW: 2.5 g/L, 5 g/L. and 7.5 g/L. We observed that adding ECN of 5 g/L during anaerobic digestion improved biogas production. Further, at this concentration, the methane concentration on the biogas was 64%, while on the control samples (without ECN) was only 0.09%. These findings suggested the benefit of ECN supplementation during anaerobic digestion of TLW for biogas production.